2006
DOI: 10.1007/s00404-006-0208-1
|View full text |Cite
|
Sign up to set email alerts
|

Water birth, more than a trendy alternative: a prospective, observational study

Abstract: Water birth is a valuable and promising alternative to traditional delivery methods. The maternal and fetal outcomes were similar to traditional land births. However, currently there still exist some deficits in the scientific evaluation of its safety. Therefore, the selection of a low-risk collective is essential to minimize the risks with the addition of strictly maintained guidelines and continuous intrapartum observation and fetal monitoring. Based on our results and the literature, water births are justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 23 publications
3
49
0
1
Order By: Relevance
“…Other studies have also indicated that immersion in water during labor and delivery can reduce the analgesic requirements of the mother without adverse effects on the neonate [2-4,14,15]. Our results also showed that VAS pain scores were significantly lower in the water immersion group than in the conventional labor group.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Other studies have also indicated that immersion in water during labor and delivery can reduce the analgesic requirements of the mother without adverse effects on the neonate [2-4,14,15]. Our results also showed that VAS pain scores were significantly lower in the water immersion group than in the conventional labor group.…”
Section: Discussionsupporting
confidence: 74%
“…The potential for adverse neonatal outcomes has been an argument against water immersion and water births [19]. However, a number of studies have reported equivalent or better neonatal outcomes (Apgar scores, requirement for neonatal intensive care unit admission) for women that have undergone water immersion and water births as compared with those who have undergone conventional labor and delivery [2-4,20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers and providers differentiate criteria that preclude waterbirth but not immersion during labor. These include history of a shoulder dystocia, history of severe postpartum hemorrhage (> 1000 mL), meconium‐stained amniotic fluid, suspected macrosomia, or fetal growth restriction …”
Section: Practice Principles For Waterbirthmentioning
confidence: 99%
“…[41][42][43] Bacteriological testing for GBS carriage is not recommended for women with preterm rupture of membranes. IAP should be given once labour is confirmed or induced irrespective of GBS status.…”
mentioning
confidence: 99%